A Review Paper on Plant Virus Detection Methods (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because fast changing climate facilitates the  movement of viruses as well as their hosts, also vectors, from  one nation or region to another, early and correct  identification of plant viruses is critical to their management.  The diagnosis of viral diseases is becoming increasingly  crucial. So because indications of viral infections are not  always distinct and might be mistaken with those of abiotic  stressors, a suggestive diagnosis may not be the best  approach. Agriculture is vital to every country's economy,  and bacteria, fungus, and viruses represent a major danger to  crops. Viruses, unlike any other ailment, are to blame for a  significant share of the reduction in agricultural production.  A variety of diagnostic procedures can be used to identify  these viruses. There are direct and indirect solutions to this  problem, each with its own set of benefits and drawbacks.  The infection of the causative pathogen can be used to create  diagnostic procedures. Observation of signals in indicator  crops, electron microscopy, or serological techniques  including such enzyme-linked Immunosorbent Assay have  all been sometimes used identify virus in plants. They can be  used to identify the best timing to start utilizing ELISA or  PCR assays to detect plant viruses. Plant viruses can be  recognized and treated if found early enough, result in a  virus-free crop in the future. These techniques (ELISA or  PCR) will become the future standards in diagnostics as the  cost of these techniques (ELISA or PCR) decreases.
Keywords: DNA; Detection; Disease; ELISA; Pathogen; RNA; Virus